Finnish folklore atlas - Sarmela, Matti (Helsinki, Finland : Matti Sarmela, 2009)
99 maps on the ethnic culture of the peoples of Finland and Karelia: rites, customs, beliefs, narratives and poetry in archaic meter. The Atlas is a unique cartographical analysis of the culture of northern hunter-gatherers, Swidden cultivators and agrarian peasants and their adaptation to the environment of their times; the cultural periods of shamans, sorcerers and Christian villages
Title from container
Includes bibliographical references
System requirements: Adobe Acrobat Reader
Keywords: Ethnology -- Finland -- Maps; Folklore -- Finland -- Maps; Finland -- Social life and customs -- Maps